Addressing Cultural And Religious Intolerance For Effective Teaching, Learning And Peace Of The Primary School Children In Zimbabwe: A Case Study Of Shurugwi District Schools - Saiden, Thondhlana; D., Makawa James. (Advances in Social Sciences Research Journal, 2017)
The study was aimed at establishing the effect of religion and culture on effective teaching, learning and peace. It was a follow up study of a similar study undertaken in Gweru District primary schools. The study was qualitative and used a case study design. The study was informed by ethnography. The sample for the study consisted of 93 teachers, 60 primary school children, 1 District schools’ inspector and 2 conflict resolution experts. The respondents were conveniently chosen in the mean while conflict resolution experts were chosen by snow-balling. The findings were that ethnocentrism and xenocentrism was rampant, negatively affecting effective teaching, learning and peace in the primary schools. It was also found out there was no religious and cultural appreciation impacting negatively on teaching, learning and peace. Fundamentalism also exists. It was recommended inter-alia that multicultural education and inter-faithism be introduced in the primary school system.